(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research seeks to read the verbal paradox at the primitive level; The paradox in it is based on the contrast between multiple words in a special context of the poetic text structure; The contrast between the words reveals multiple indications, expressing the intention of employing the paradox, and shows the semantic evasions that the words carry between the superficial and deep structures. Accordingly, the great paradoxical contrasts do not stop at the meeting of two opposing meanings in one word, as in the paradoxes of minor contrasts. Rather, the contrast extends to include a larger verbal structure, and the contrast may include more than two opposing words, and it is necessary to leave the space for the reading text to determine the nature of that. The paradoxes of major contrasts in "Nazih Abu Afash" help to reveal different dialectics related to reality and man and take their farthest extent in revealing the conflict between man, his society and his universe, and reconsider how to look at life and its dialectics, and it is not isolated from the nature of existential thought that affected the poet’s texts